Penetapan Kadar Betametason Valerat Pada Sediaan Krim betametasone 0,1 % Secara Kromatografi Cair Kinerja Tinggi - Indriati Indriati; Ferdinan Jalung; Herviza Wulandary Pane (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Background; Medicine is used as a support in the world of health. Medicine is a material intended for use in establishing diagnoses, preventing, reducing, eliminating, curing diseases or symptoms of diseases, injuries or bodily and spiritual disorders in humans or animals, beautifying the body or parts of the human body. Objective; To validate the method of determining the level of Betamethasone Valerate using HPLC with stationary phase C18 and mobile phase methanol: water that meets the requirements of the method validation test including precision, accuracy, selectivity, linearity and sensitivity. Methods; This research is a type of Quasy Experimental research with a Pretest Posttest Nonequivalent Control Group design, namely in this design the experimental group and control group are not randomly selected, in other words this design is carried out before and after treatment. Results; The determination of levels is carried out after the method to be used has been proven valid after going through the validation test processes. The determination of levels was carried out on the five face cream samples as much as 3 totolan in each sample. The results of the level determination test showed that the five samples did not contain betamethasone valerate and triamcinolone acetonide. Conclusion; The KLT-densitometry method used to quantify the content of topical corticosteroids in Betamethasone 0.1% cream tested has met the validation parameters of ICH and AOAC includes accuracy, precision, specificity, linearity, LOD, LOQ.